Transcranial magnetic stimulation and cognitive neuroscience. - Walsh, V; Cowey, A (2000)
Transcranial magnetic stimulation has been used to investigate almost all areas of cognitive neuroscience. This article discusses the most important (and least understood) considerations regarding the use of transcranial magnetic stimulation for cognitive neuroscience and outlines advances in the use of this technique for the replication and extension of findings from neuropsychology. We also take a more speculative look forward to the emerging development of strategies for combining transcranial magnetic stimulation with other brain imaging technologies and methods in the cognitive neurosciences.